O Conselho Municipal de Educação de Porto Feliz/SP: intercorrências da gestão democrática - Silva, Petula Ramanauskas Santorum e (2021)
The central objective of this research in the area of education policy and management was to analyze the initiatives and strategies of the Municipal Council of Education (CME) were used to implement democratic management in the municipality of Porto Feliz/SP (Municipality of the RMS - Metropolitan Region of Sorocaba/SP, Sub-region 2), in light of the performance of the members of the aforementioned council for the effectiveness of the representation and guarantee of socially referenced quality. The research was delimited to the period 2017-2021, in comparison to the results of the research already carried out with the other RMS municipalities, from their respective CMEs as to the planning and implementation of the socially referenced quality between successful returns and adverse contexts, project coordinated by GEPLAGE - Group of Studies and Researches State, Politics, Planning, Evaluation and Management of Education UFSCar - Sorocaba. The project methodology was developed through qualitative research, consisting of bibliographic and documentary analysis, and data treatment through content analysis based on the works of Bardin (2011). The collection of feedback from respondents was carried out with 08 (eight) municipal education counselors from Porto Feliz / SP. The results, based on the respondents' speech and understanding of the object, showed that: the idea of democratic management appears diffusely in the official documents and statements of the respondents and municipal authorities, there are weaknesses regarding its implementation in the Municipal Council of Education of Porto Feliz/SP, especially regarding autonomy, representativeness, parity, participation and also in the performance of its deliberative functions, advisory and normative functions, and the supervisory and mobilizing functions do not even appear in their legislation, as well as vulnerabilities regarding the principles of public administration. Measures regarding democratic management mechanisms and strategies need to be studied and forwarded within the municipality.